2007
DOI: 10.1119/1.2823996
|View full text |Cite
|
Sign up to set email alerts
|

Pinhole Glasses

Abstract: Eye aberrations are commonly corrected by lenses that restore vision by altering rays before they pass through the cornea. Some modern promoters claim that pinhole glasses are better than conventional lenses in correcting all kinds of refractive defects such as myopia (nearsighted), hyperopia (farsighted), astigmatisms, and presbyopia. Do pinhole glasses really give better vision? Some ways to use this question for motivation in teaching optics have been discussed.1 For this column we include a series of exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 4 publications
(4 reference statements)
0
11
0
Order By: Relevance
“…(1995) also used dark sun glasses as a control for their estimated 94% attenuation of incident light by pinholes and similarly concluded that “the effect of the pinhole arrays was not due to light attenuation” (p. 191). Multiple pinhole glasses can also result in two or more images of each point when pupils are dilated by more than the separation between pinholes ( Colicchia, Hopf, Wiesner, & Zollman, 2008 ) which could also have disrupted depth processing. Again this possibility cannot be entirely ruled out but no participant complained of double vision during the experiment, and the effect is normally eliminated by a small change in view.…”
Section: Discussionmentioning
confidence: 99%
“…(1995) also used dark sun glasses as a control for their estimated 94% attenuation of incident light by pinholes and similarly concluded that “the effect of the pinhole arrays was not due to light attenuation” (p. 191). Multiple pinhole glasses can also result in two or more images of each point when pupils are dilated by more than the separation between pinholes ( Colicchia, Hopf, Wiesner, & Zollman, 2008 ) which could also have disrupted depth processing. Again this possibility cannot be entirely ruled out but no participant complained of double vision during the experiment, and the effect is normally eliminated by a small change in view.…”
Section: Discussionmentioning
confidence: 99%
“…In models with a pinhole aperture, all focus defects become less noticeable in bright light. 5 This effect is similar to an eye with the pupil closing to a pinhole in which the depth of field will be enhanced, and the blurredness of image is reduced without improving focusing.…”
Section: Images Of Bright Objectsmentioning
confidence: 93%
“…Although several review articles have been published in a similar topic recently, these considered only contact lenses and IOLs. 11,[23][24][25][26]…”
Section: Methodsmentioning
confidence: 99%
“…6,7 A pinhole, say of 1-mm diameter, placed close to the eye will reduce the width of the bundle of rays entering the eye from each object point and reduce the area of retinal blur, thus improving vision. [6][7][8][9][10][11] Diffraction starts to seriously adversely affect image quality as pupil size decreases, and there may be no benefit in smaller pupil sizes such as 0.75 mm and 0.5 mm. 6 There is also a decrease in the retinal illumination that may affect vision adversely in lowillumination environments.…”
mentioning
confidence: 99%